(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the methodology for sorting and guiding young freestyle wrestlers by weight-height indicators. This methodology helps to distinguish young wrestlers into types by height and weight weight, and prepare them for sports wrestlers. The article describes the height-length and weight-weight averages of highly skilled wrestlers and breaks them down into model characteristics. According to the article, the model characteristics of young freestyle wrestlers by body size, their morphological characteristics, and weight-height indexes are taxable. The above data is used in determining model characteristics on sport wrestlers and predicting future height growth indicators.